Molecular and Cellular Mechanisms Involved in Host-Specific Resistance to Cyst Nematodes in Crops - Zheng, Qi; Putker, Vera; Goverse, Aska (Frontiers in Plant Science, 2021)
Cyst nematodes are able to infect a wide range of crop species and are regarded as a major threat in crop production. In response to invasion of cyst nematodes, plants activate their innate immune system to defend themselves by conferring basal and host-specific defense responses depending on the plant genotype. Basal defense is dependent on the detection of pathogen-associated molecular patterns (PAMPs) by pattern recognition receptors (PRRs), while host-specific defense mainly relies on the activation of canonical and non-canonical resistance (R) genes or quantitative trait loci (QTL). Currently, application of R genes and QTLs in crop species is a major approach to control cyst nematode in crop cultivation. However, emerging virulent cyst nematode field populations are threatening crop production due to host genetic selection by the application of a limited set of resistance genes in current crop cultivars. To counteract this problem, increased knowledge about the mechanisms involved in host-specific resistance mediated by R genes and QTLs to cyst nematodes is indispensable to improve their efficient and sustainable use in field crops. Despite the identification of an increasing number of resistance traits to cyst nematodes in various crops, the underlying genes and defense mechanisms are often unknown. In the last decade, indebt studies on the functioning of a number of cyst nematode R genes and QTLs have revealed novel insights in how plants respond to cyst nematode infection by the activation of host-specific defense responses. This review presents current knowledge of molecular and cellular involved in the recognition of cyst nematodes, the activation of defense signaling and resistance response types mediated by R genes or QTLs. Finally, future directions for research are proposed to develop management strategies to better control cyst nematodes in crop cultivation.